Evaluation of Systemic Inflammatory Response in Cardiovascular Surgery via Interleukin-6, Interleukin-8, and Neopterin - Uyar, Ihsan Sami; Onal, Suleyman; Uysal, Ayhan; Ozdemir, Ugur; Burma, Oktay; Bulut, Vedat (Forum Multimedia Publishing, Llc, 2014)
Aim: The aim of this study was to evaluate the serum levels of interleukin-6 (IL-6), IL-8, and neopterin as a sign of systemic inflammatory response syndrome after open-heart surgery. In this study, we evaluated the influences on the levels of IL-6, IL-8, and neopterin of coronary artery bypass grafting (CABG) and valve replacement surgeries with and without the use of extracorporeal circulation (ECC). Materials and Methods: This prospective study was performed in 30 patients. In this study, we evaluated patients who underwent valve replacement surgery (group 1, n = 10), CABG with ECC (group 2, n = 10), or CABG using the beating-heart technique (group 3, n = 10). With the Human Investigation Ethics Committee consent, blood samples were obtained from the patients before the surgery (T0) and after 1 hour (T1), 4 hours (T2), 24 hours (T3), and 48 hours (T4) of protamine injection. IL-6, IL-8, and neopterin levels were measured using commercial enzyme-linked immunosorbent assay kits. Results: The demographic data and preoperative and operative characteristics of the patients were similar. Neopterin IL-6 and IL-8 levels significantly increased first at the fourth hour after the surgery. When compared to the levels before the surgery, this increase was statistically significant. Unlike the other 2 groups of patients, those who experienced CABG with the beating-heart technique (group 3) had decreased neopterin levels at the first hour after the surgery, but this decrease was not statistically significant. Neopterin levels increased later in the OPCAB group, but these increased levels were not as high as the neopterin levels of groups 1 and 2. Neopterin reached maximum levels at the 24th hour and, unlike groups 1 and 2, in group started to decrease at the 48th. Conclusions: Complement activation, cytokine production, and related cellular responses are important factors during open-heart surgery. It is certain that ECC activates the complement systems, and activated complement proteins cause the production of several cytokines. In our study, neopterin levels in patients who underwent beating-heart method surgery were lower than those in the other groups, and these levels started to decrease at the 48th hour. These data suggest that the systemic inflammatory response was less activated in that patient group. The beating-heart method might be an important alternative in CABG surgery to minimize the complications and mortality related to surgery.
Keywords: Cardiopulmonary Bypass; Proinflammatory Cytokines; Cardiac-Surgery; Coated Circuits; Dysfunction; Myocardium; Expression; Cabg; Il-8